Mechanism of ALKBH5 mediated m6A regulation of Galectin-9 in the invasion, migration, and proliferation of endometrial stromal cell - WANG Fang; LIU Hengwei; LIANG Jiaxin; WANG Xiwen (Yixue xinzhi zazhi)
Objective To investigate the potential role of ALKBH5-mediated m6A modification of Galectin-9 in the invasion, migration, and proliferation of endometrial stromal cells (ESCs) in endometriosis.Methods A total of 20 normal endometrial (NC) specimens and 20 ectopic endometrial (EC) specimens from patients with endometriosis were obtained. The expression of ALKBH5 and Galectin-9 in tissues was detected using immunohistochemistry, qRT-PCR and Western blot. In addition, 10 cases of normal proliferative endometrial tissues were collected and primary ESCs were extracted, and the mechanism of ALKBH5 in regulating the level and mRNA expression of Galectin-9 m6A was investigated by bioinformatics analysis, methylated RNA immunoprecipitation (MeRIP), and RIP assay. After ALKBH5 overexpression, the proliferation, migration, and invasion abilities of ESCs were determined by Transwell and cell counting kit-8 (CCK-8) assays. The effect of ALKBH5 on ESCs invasion, migration, and proliferation was investigated.Results Compared with NC tissues, the expression of ALKBH5 and Galectin-9 was increased in EC tissues from patients with endometriosis (P